Landfast ice in the Kara Sea stabilizes the Arctic halocline and may slow down Atlantification of the Eurasian Basin - Yuqing Liu; Martin Losch; L. Bruno Tremblay; Markus Janout (Communications Earth & Environment)
Abstract Observations show an Atlantification of the Eurasian Basin of the Arctic Ocean, with deeper penetration, shoaling, and ventilation of Atlantic waters in the eastern Arctic and an associated weakening of the cold halocline layer. These processes have a profound impact on the sea ice cover above and potentially on the transition of the Arctic to a seasonal ice cover. Here we show, using a coupled ice-ocean model, that a proper simulation of the landfast ice cover in the relatively small but deeper peripheral Kara Sea has a disproportionately large influence on the halocline stability in the Eurasian Basin and beyond. Specifically, landfast ice in the Kara Sea reduces ice growth and therefore salt rejection into the surface ocean. This negative salinity anomaly is advected eastward with a coastal current along the continental shelf in the Makarov Basin and then out of the Arctic through Fram Strait by the Transpolar Drift Stream on timescales of less than ten years. Global Climate Models, however, do not yet include landfast ice parameterizations. Therefore, they are missing this key process affecting the halocline stability, Atlantification of the Makarov Basin, and potentially the timing of a seasonally ice-free Arctic.